Apoplast redox metabolism: Effect of acetovanillone (apocynin) and acetosyringone, on their co-oxidation and redox properties. (April 2020) - Baker, C. Jacyn; Smith, Jodi; Rice, Clifford
Abstract: A common response of plant leaves and roots to stress, biotic or abiotic, is the oxidative burst. In leaves, this results in reactive oxygen species being produced within the apoplast, the space surrounding the responding cells. A second response that occurs in the tobacco apoplast during this period is the production and accumulation of phenolic metabolites. The interaction of these redox active metabolites should have major effects on the redox potential of the apoplast and subsequently affect the outcome of the plant tissue. To begin to understand the effects of these responses on the redox potential, two induced phenolics, acetovanillone (AV) and acetosyringone (AS) were studied in vitro with peroxidase and H2 O2, all of which are present in the tobacco apoplast. While both phenolics were observed to be substrates for peroxidase, AV was found to react 10x faster than AS. The oxidation of AV resulted in an increase of the redox potential to a maximum of 0.35 V. The oxidation of AS resulted in an increase to a maximum of 0.55 V. Interestingly, the redox potential was not proportional to the oxidation of either phenolic. It was found that when present together, co-oxidation occurs with the faster acting AV as a catalyst to oxidize AS. This has an immediate effect on the redox potential. The rate of AS oxidation is dependent on the AV concentration and thus so is the redox potential reaching 4.5 V. The results suggest that these phenolics could play a role in the regulation of the apoplast redox potential during the early stages of stress. Highlights: Co-oxidation of apoplast phenolics can increase the redox potential. Apoplast phenolics can act as prooxidants rather than antioxidants. Apoplast phenolics produce relatively stable free radicals.